Two-Sided Market and Game Console Vendors - Fang Cheng, Terry

Tragedy of the Common Cloud - Game Theory on the Infrastructure-as-a-Service Market - Künsemöller, Jörn

Towards a Flexible and Privacy-Preserving Reputation System for Markets of Composed Services - Brangewitz, Sonja; Jungmann, Alexander; Petrlic, Ronald; Platenius, Marie Christin (Proceedings of the 6th International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
One future goal of service-oriented computing is to realize global markets of composed services. On such markets, service providers offer services that can be flexibly combined with each other. However, most often, market participants are not able to individually estimate the quality of traded services in advance. As a consequence, even potentially profitable transactions between customers and providers might not take place. In the worst case, this can induce a market failure. To overcome this problem, we propose the incorporation of reputation information as an indicator for expected service quality. We address On-The-Fly Computing as a representative environment of markets of composed services. In this environment, customers provide feedback on transactions. We present a conceptual design of a reputation system which collects and processes user feedback, and provides it to participants in the market. Our contribution includes the identification of requirements for such a reputation system from a technical and an economic perspective. Based on these requirements, we propose a flexible solution that facilitates the incorporation of reputation information into markets of composed services while simultaneously preserving privacy of customers who provide feedback. The requirements we formulate in this paper have just been partially met in literature. An integrated approach, however, has not been addressed yet.

The Interaction of Signals: A Fuzzy set Analysis of the Video Game Industry - Kaimann, Daniel; Cox, Joe
Customers continuously evaluate the credibility and reliability of a range of signals both separately and jointly. However, existing econometric studies pay insufficient attention to the interactions and complex combinations of these signals, and are typically limited as a result of difficulties controlling for multicollinearity and endogeneity in their data. We develop a novel theoretical approach to address these issues and study different signaling effects (i.e., word-of-mouth, brand reputation, and distribution strategy) on customer perceptions. Using data on the US video games market, we apply a fuzzy set qualitative comparative analysis (fsQCA) to account for cause-effect relationships. The results of our study address a number of key issues in the economics and management literature. First, our results support the contention that reviews from professional critics act as a signal of product quality and therefore positively influence unit sales, as do the discriminatory effects of prices and restricted age ratings. Second, we find evidence to support the use of brand extension strategies as marketing tools that create spillover effects and support the launch of new products.

The Impact of Customer Reviews and Reputation on Hotel Prices - Holzweißig, Lena

The Economics of Individual Behavior in Competitive Environments: Empirical Evidence from Real-Life Tournaments - Scheel, Friedrich

Template Embedding: Using Application Architecture to Allocate Resources in Distributed Clouds - Keller, Matthias; Robbert, Christoph; Karl, Holger (Proceedings of 7th International Conference on Utility and Cloud Computing (UCC))
In distributed cloud computing, application deployment across multiple sites can improve quality of service. Recent research developed algorithms to find optimal locations for virtual machines. However, those algorithms assume to have either single-tier applications or a fixed number of virtual machines – a strong simplification of reality. This paper investigates the placement and scaling of complex application architectures. An application is dynamically scaled to fit both the current demand situation and the currently available infrastructure resources. We compare two approaches: The first one is based on virtual network embedding. The second approach is a novel method called Template Embedding. It is based on a hierarchical 1-allocation hub flow problem and combines applica- tion scaling and embedding in one step. Extensive experiments on 43200 network configurations showed that Template Embedding outperforms virtual network embedding in all cases in three metrics: success rate, solution quality, and runtime. This positive result shows that template embedding is a promising approach for distributed cloud resource allocation.

Surrounding robots -- A discrete localized solution for the intruder problem - Blazovics, Laszlo; Lukovszki, Tamas; Forstner, Bertalan (Journal of Advanced Computational Intelligence and Intelligent Informatics)
Decentralized algorithms are often used in the cooperative robotics field, especially by large swarm systems. We present a distributed algorithm for a problem in which a group of autonomous mobile robots must surround a given target. These robots are oblivious, i.e., they have no memory of the past. They use only local sensing and need no dedicated communication among themselves. We introduce, then solve the problem in which the group of autonomous mobile robots must surround a given target – we call it the “discrete multiorbit target surrounding problem” (DMTSP). We evaluate our solution using simulation and prove that our solution invariably ensures that robots enclose the target in finite time.

Struktur und algorithmische Bestimmung stabiler Matchings in one-to-one Matching Märkten - Ebel, Olga

Strategic and Cooperative Games in Network Economics - Röhl, Nils

Specifying and Placing Chains of Virtual Network Functions - Dräxler, Sevil; Keller, Matthias; Karl, Holger (Proceedings of the 3rd International Conference on Cloud Networking (CloudNet))
Network appliances perform different functions on network flows and constitute an important part of an operator’s network. Normally, a set of chained network functions process network flows. Following the trend of virtualization of networks, virtualization of the network functions has also become a topic of interest. We define a model for formalizing the chaining of network functions using a context-free language. We process deployment requests and construct virtual network function graphs that can be mapped to the network. We describe the mapping as a Mixed Integer Quadratically Constrained Program (MIQCP) for finding the placement of the network functions and chaining them together considering the limited network resources and requirements of the functions. We have performed a Pareto set analysis to investigate the possible trade-offs between different optimization objectives.

Simulating load-dependent operation of picocells - Roeske, Daniel

Signalisieren und Screening in Arbeitsmärkten - die Experimente von Brandts & Holt und Kübler et. al - Kaiser, Sarah

Secure Distributed Data Structures for Peer-to-Peer-based Social Networks - Janiuk, Jens; Mäcker, Alexander; Graffi, Kalman (Proceedings of the International Conference on Collaboration Technologies and Systems (CTS))
Online social networks are attracting billions of nowadays, both on a global scale as well as in social enterprise networks. Using distributed hash tables and peer-to-peer technology allows online social networks to be operated securely and efficiently only by using the resources of the user devices, thus alleviating censorship or data misuse by a single network operator. In this paper, we address the challenges that arise in implementing reliably and conveniently to use distributed data structures, such as lists or sets, in such a distributed hash-tablebased online social network. We present a secure, distributed list data structure that manages the list entries in several buckets in the distributed hash table. The list entries are authenticated, integrity is maintained and access control for single users and also groups is integrated. The approach for secure distributed lists is also applied for prefix trees and sets, and implemented and evaluated in a peer-to-peer framework for social networks. Evaluation shows that the distributed data structure is convenient and efficient to use and that the requirements on security hold.

Scheduling Shared Continuous Resources on Many-Cores - Brinkmann, Andre; Kling, Peter; Meyer auf der Heide, Friedhelm; Nagel, Lars; Riechers, Sören; Suess, Tim (Proceedings of the 26th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We consider the problem of scheduling a number of jobs on $m$ identical processors sharing a continuously divisible resource. Each job j comes with a resource requirement r_j \in {0,1}. The job can be processed at full speed if granted its full resource requirement. If receiving only an x-portion of r_j, it is processed at an x-fraction of the full speed. Our goal is to find a resource assignment that minimizes the makespan (i.e., the latest completion time). Variants of such problems, relating the resource assignment of jobs to their processing speeds, have been studied under the term discrete-continuous scheduling. Known results are either very pessimistic or heuristic in nature.In this paper, we suggest and analyze a slightly simplified model. It focuses on the assignment of shared continuous resources to the processors. The job assignment to processors and the ordering of the jobs have already been fixed. It is shown that, even for unit size jobs, finding an optimal solution is NP-hard if the number of processors is part of the input. Positive results for unit size jobs include an efficient optimal algorithm for 2 processors. Moreover, we prove that balanced schedules yield a 2-1/m-approximation for a fixed number of processors. Such schedules are computed by our GreedyBalance algorithm, for which the bound is tight.

RSA-Full Domain Hash Revisited - Rath, Timo
RSA Full Domain Hash ist im Zufallsorakelmodell ein EUF-CMA sicheres Signaturverfahren (existentially unforgeable under chosen-message attacks). Der Sicherheitsbeweis wird unter anderem in der Vorlesung Einführung in die Kryptographie vorgestellt. Auch bei einer genaueren Analyse verliert man bei der Reduktion einen Faktor \nicefrac{1}{q_{s}}(wobei q_{s}die Anzahl der Anfragen an das Signaturorakel darstellt), was für die Praxis in relativ großen Systemparametern (RSA-Modul) resultiert [1].Seit der Veröffentlichung von [2] wurde geglaubt, dass der Faktor \nicefrac{1}{q_{s}}optimal ist. Erst zehn Jahre später offenbarten die Autoren von [3] einen Fehler in [2] und zeigten eine bessere Reduktion allerdings unter einer etwas stärkeren Sicherheitsannahme.Die Ergebnisse aus [3] lassen sich auf PSS-Verfahren (Probabilistic Signature Scheme), das z.B. in PKCS #1 benutzt wird, übertragen und sind somit von großer Bedeutung für die Praxis. Weiterhin sind die in den Beweisen verwendete Techniken nützlich auch bei anderen kryptographischen Verfahren.In Rahmen dieser Arbeit sollen die entsprechenden Sicherheitsbeweise aufgearbeitet und dessen Auswirkungen für die Praxis analysiert werden.[1] J.S. Coron, “On the Exact Security of Full Domain Hash”, CRYPTO 2000. LNCS 1880, pp. 229-235, 2000.[2] J.S. Coron, “Optimal security proofs for PPS and other signature schemes”, EUROCRYPT 2002. LNCS 2332, pp 272-287, 2002.[3] S.A. Kakvi and E. Kiltz, “Optimal Security Proofs for Full Domain Hash, Revisited”, in EUROCRYPT 2012. LNCS 7237, pp 537-553, 2012.

Routing Games with Progressive Filling - Harks, Tobias; Höfer, Martin; Schewior, Kevin; Skopalik, Alexander (Proceedings of the 33rd Annual IEEE International Conference on Computer Communications (INFOCOM'14))
Max-min fairness (MMF) is a widely known approach to a fair allocation of bandwidth to each of the users in a network. This allocation can be computed by uniformly raising the bandwidths of all users without violating capacity constraints. We consider an extension of these allocations by raising the bandwidth with arbitrary and not necessarily uniform time-depending velocities (allocation rates). These allocations are used in a game-theoretic context for routing choices, which we formalize in progressive filling games (PFGs).We present a variety of results for equilibria in PFGs. We show that these games possess pure Nash and strong equilibria. While computation in general is NP-hard, there are polynomial-time algorithms for prominent classes of Max-Min-Fair Games (MMFG), including the case when all users have the same source-destination pair. We characterize prices of anarchy and stability for pure Nash and strong equilibria in PFGs and MMFGs when players have different or the same source-destination pairs. In addition, we show that when a designer can adjust allocation rates, it is possible to design games with optimal strong equilibria. Some initial results on polynomial-time algorithms in this direction are also derived.

Response Time-Optimized Distributed Cloud Resource Allocation - Keller, Matthias; Karl, Holger (Proceedings of the SIGCOMM workshop on Distributed cloud computing)
In the near future many more compute resources will be available at different geographical locations. To minimize the response time of requests, application servers closer to the user can hence be used to shorten network round trip times. However, this advantage is neutralized if the used data centre is highly loaded as the processing time of re- quests is important as well. We model the request response time as the network round trip time plus the processing time at a data centre.We present a capacitated facility location problem formal- ization where the processing time is modelled as the sojourn time of a queueing model. We discuss the Pareto trade-off between the number of used data centres and the resulting response time. For example, using fewer data centres could cut expenses but results in high utilization, high response time, and smaller revenues.Previous work presented a non-linear cost function. We prove its convexity and exploit this property in two ways: First, we transform the convex model into a linear model while controlling the maximum approximation error. Sec- ond, we used a convex solver instead of a slower non-linear solver. Numerical results on network topologies exemplify our work.

Reputationssysteme für zusammengesetzte Dienstleistungen - Pahl, David

Reducing Energy Consumption of Radio Access Networks - Herlich, Matthias
Radio access networks (RANs) have become one of the largest energy consumers of communication technology [LLH+13] and their energy consumption is predicted to increase [FFMB11]. To reduce the energy consumption of RANs different techniques have been proposed. One of the most promising techniques is the use of a low-power sleep mode. However, a sleep mode can also reduce the performance. In this dissertation, I quantify how much energy can be conserved with a sleep mode and which negative effects it has on the performance of RANs. Additionally, I analyze how a sleep mode can be enabled more often and how the performance can be kept high. First, I quantify the effect of power-cycle durations on energy consumption and latency in an abstract queuing system. This results in a trade-off between energy consumption and latency for a single base station (BS). Second, I show that considering a network as a whole (instead of each BS individually) allows the energy consumption to be reduced even further. After these analyses, which are not specific for RANs, I study RANs for the rest of the dissertation. RANs need to both detect and execute the requests of users. Because detection and execution of requests have different requirements, I analyze them independently. I quantify how the number of active BSs can be reduced if the detection ranges of BSs are increased by cooperative transmissions. Next, I analyze how more BSs can be deactivated if the remaining active BSs cooperate to transmit data to the users. However, in addition to increasing the range, cooperative transmissions also radiate more power. This results in higher interference for other users which slows their transmissions down and, thus, increases energy consumption. Therefore, I describe how the radiated power of cooperative transmissions can be reduced if instantaneous channel knowledge is available. Because the implementation in real hardware is impractical for demonstration purposes, I show the results of a simulation that incorporates all effects I studied analytically earlier. In conclusion, I show that a sleep mode can reduce the energy consumption of RANs if applied correctly. To apply a sleep mode correctly, it is necessary to consider power-cycle durations, power profiles, and the interaction of BSs. When this knowledge is combined the energy consumption of RANs can be reduced with only a slight loss of performance. Because this results in a trade-off between energy consumption and performance, each RAN operator has to decide which trade-off is preferred.